Well-being is dead, long live well-being! - Piper, Mark (2025)
My primary concern in this paper is with how answering a central metaethical question about well-being impacts work on substantive theories of well-being. Specifically, I argue that well-being invariantism is a priori untenable and hence that any attempt to establish one or more substantive prudential goods as the ‘essence’ of well-being is doomed to failure. I further argue that a priori considerations establish the truth of well-being contextualism. Importantly, the truth of well-being contextualism does not undermine the possibility of making objective, substantive well-being claims. Once a context or orientation is established, the relevant standards become clear and derivative objective judgments are possible. The upshot of this paper is that philosophers should abandon the attempt to establish any invariant substantive claims about well-being as such (well-being invariantism is dead). Instead, we should focus on clarifying the most important contexts in which we wish to make well-being claims and seek to make progress in those (long live well-being).